A homozygous loss-of-function mutation in GP1BB causing variable clinical phenotypes in a family with Bernard–Soulier syndrome. Issue 5 (July 2021) - Al-Numair, Nouf; Ramzan, Khushnooda; Alquait, Laila; Alshehri, Meshal; Imtiaz, Faiqa; Owaidah, Tarek
Abstract : N/A: Bernard–Soulier syndrome is a rare autosomal recessive bleeding disorder and has a low incidence. Bernard–Soulier syndrome is caused by the deficiency of glycoprotein GPIb-V-IX complex, a receptor for von Willebrand factor and is characterized by thrombocytopenia, giant platelets and bleeding tendency. We are reporting three members of a same family with variable phenotypic clinical presentation. The index case is a 20-year-old boy who has a frequent presentation with epistaxis, and low platelet counts (25 × 10 9 /l). He had been hospitalized multiple times and received platelet transfusions. His brother and cousin reported bleeding symptoms with less frequent medical intervention. Genetic analysis by next-generation sequencing identified a homozygous GP1BB variant (c.423C>A:p.Cys141Ter), which segregated amongst the family members. The results led us to an improved insight into the disease for this family with variable phenotypic expression, in addition to the identification of a variant for further structural and functional characterization.